PROGRAM SIMULASI KOMPUTER UNTUK MENINGKATKAN RENDEMEN PENGGERGAJIAN - Osly Rachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
The computer simulation programs for increasing lumber recovery are presented in this paper. These programs were created for sawing logs with live sawing, half sawing, and semi-quarter sawing patterns, and convening the sawn limber into blanks using turbo basic language version 1, 1. The log model used was a truncated cylinder to represent the real logs.The best opening first (BOF) of logs is computed by entering data of log factors such as diameter and length, and sawing factors such as saw kerf, sawn limber thickness, allowance for sawing thickness, blank width, and allowance for sawing width.For several runs on computer under any circumtances the program produced nominal lumber and blank recovery ranging 73-76 % and 83 - 89 %, respectively, the values of shrinkage allowance, planing allowance and sawing variation have been included in nominal lumber recovery.